2003
DOI: 10.1016/s0022-5223(02)73291-1
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of low hematocrit during cardiopulmonary bypass in the adult: should current practice be changed?

Abstract: Increased hemodilution severity during cardiopulmonary bypass was associated with worse perioperative vital organ dysfunction/morbidity and increased resource use, as well as greater short- and intermediate-term mortality. We speculate that these results derive from inadequate oxygen delivery causing ischemic and/or inflammatory vital organ injury, as recently demonstrated intravitally in cerebral tissues. Although this analysis of a large observational study offers evidence linking low on-pump hematocrit valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
259
2
13

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 379 publications
(285 citation statements)
references
References 19 publications
11
259
2
13
Order By: Relevance
“…However, recent clinical and experimental studies have demonstrated that acute hemodilution can reduce tissue oxygen delivery to vital organs and increase organ injury and mortality. 2,[11][12][13][14] These data provide evidence that acute normovolemic hemodilution may be detrimental. The focus of the current review is on the risk associated with acute hemodilution (normovolemia) and not hemorrhage and hypotension (hypovolemia).…”
Section: The Risk Of Anemiamentioning
confidence: 72%
See 3 more Smart Citations
“…However, recent clinical and experimental studies have demonstrated that acute hemodilution can reduce tissue oxygen delivery to vital organs and increase organ injury and mortality. 2,[11][12][13][14] These data provide evidence that acute normovolemic hemodilution may be detrimental. The focus of the current review is on the risk associated with acute hemodilution (normovolemia) and not hemorrhage and hypotension (hypovolemia).…”
Section: The Risk Of Anemiamentioning
confidence: 72%
“…Despite these adaptations, increasing clinical evidence supports a strong association between anemia, increased organ injury, and mortality. [1][2][3][4][5][6][7][8][9][10] With the advent of modern medical intervention, the initial treatment of acute blood loss is fluid resuscitation with crystalloid and/or colloid. This treatment has led to an increased incidence of normovolemic hemodilution (hemodilution) in many clinical settings, including the operating room and intensive care unit.…”
Section: The Risk Of Anemiamentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6] One of the most common causes of acute anemia is acute blood loss and fluid resuscitation (hemodilution). Therefore, we have adopted a model of acute hemodilutional anemia to study the cerebral gene responses.…”
Section: Introductionmentioning
confidence: 99%